2001
DOI: 10.1007/bf02693804
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive localization of infrainguinal arterial occlusive disease in diabetics

Abstract: A retrospective review of 101 diabetics without aortoiliac disease was carried out to analyze the ability of various noninvasive tests to predict the level of significant (>50% stenosis) infrainguinal arterial disease. Patients were studied with anklebrachial indices (ABI), toebrachial indices (TBI), segmental pulse volume recordings (PVR), segmental pressures (SEGP), segmental Doppler waveforms (DWF), and arteriography. Results were classified as normal, disease at the femoropopliteal level, infrapopliteal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The International Consensus on the Diabetic Foot (ICDF) guidelines suggested that an ABPI of 1.15 be the upper limit above which measurements are deemed unreliable (6). The TBI is then an alternative test, but the influence of arterial calcification and neuropathy on toe pressures is uncertain (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The International Consensus on the Diabetic Foot (ICDF) guidelines suggested that an ABPI of 1.15 be the upper limit above which measurements are deemed unreliable (6). The TBI is then an alternative test, but the influence of arterial calcification and neuropathy on toe pressures is uncertain (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The Toe Brachial Index (TBI) is a possible alternative to ABPI, however the microvasculature is not immune from calcification 7 , 9 and the TBI is subject to the same limitations as ABPI when ulcers, calluses, fragile skin and toe amputations are present. 10 …”
Section: Introductionmentioning
confidence: 99%
“…The Toe Brachial Index (TBI) is a possible alternative to ABPI, however the microvasculature is not immune from calcification 7,9 and the TBI is subject to the same limitations as ABPI when ulcers, calluses, fragile skin and toe amputations are present. 10 The late diagnosis or undetected progression of PAD can shorten the available window for preventative management having costly impacts upon a patient's quality of life and life expectancy, along with healthcare budgets; current estimates for diabetic care equate to 10% of NHS expenditure. 11 With the limitations of ABPI/TBI in mind, an alternative to cuff compression techniques is therefore ideal and the use of DUS derived blood waveform analysis may be the answer.…”
Section: Introductionmentioning
confidence: 99%